DIFFERENT SHAPES OF MEGAKARYOCYTES IN ESSENTIAL THROMBOCYTHEMIA - Faraz, Maria; Mansoori, Huma; Ali, Maria; Asad Ali, Sidra (Journal of Ayub Medical College Abbottabad, 2022)
Essential thrombocytopenia is the myeloproliferative neoplasm associated with the JAK2/CALR/MPL mutation. It is characterized by an increase in thrombocytes and abnormal megakaryocytes. WHO established the diagnostic criteria for diagnosing the myeloproliferative disorder, which is the combination of molecular, clinical, and histological findings. The appearance of megakaryocytes on bone marrow biopsy is the distinguishing feature to identify myeloproliferative neoplasm, and this short review would like to emphasize the presentation of megakaryocytes in bone marrow biopsy.